Hubungan antara Karakteristik Pasien dan Terapi terhadap Nilai Retensi di RSJ Menur Surabaya - Arifani Siswi Diasari; Antonius Adji Prayitno Setiadi; Lila Nurmayanti (JURNAL ILMU KEFARMASIAN INDONESIA, 2019)
Methadone maintenance therapy program (MMTP) is the government's efforts to reduce drug abuse in Indonesia.The MMTP success parameters can be seen from the retention rate which is the length of time patients undergo methadone maintenance therapy after receiving stabilization therapy (administration of methadone for 6 weeks or 42 days). This study aimed to determine the relationshipof the patientscharacteristics and therapy to the retention rate in Menur Psychiatric Hospital Surabaya. This cross-sectional study was conducted retrospectively by reviewed the patient’s medical record dan involved 41 subjects who were selected by consecutive sampling. Patient characteristics and therapy was analyzed descriptively and the variables relationship with retention rate was analyzed by using Spearman’s correlation test.The results showed the retention rate at 6 months (4.9%), 9 months (12.2%), 12 months (19.5%), 24 months (26.8%), 36 months (26.8%) , 48 months (4.9%) and 60 months (4.9%). According to Spearman's correlation test, the smallest maintenance dose shows a significant correlation to the retention rate (p = 0.036 with sufficient correlation r = -0.382). Therefore, the selection of the smallest dose in patients undergoing MMTP needs a particular concern to increase the successfulness of this program, which is indicated by the retention rate in this study.Methadone maintenance therapy program (MMTP) is the government's efforts to reduce drug abuse in Indonesia.The MMTP success parameters can be seen from the retention rate which is the length of time patients undergo methadone maintenance therapy after receiving stabilization therapy (administration of methadone for 6 weeks or 42 days). This study aimed to determine the relationshipof the patientscharacteristics and therapy to the retention rate in Menur Psychiatric Hospital Surabaya. This cross-sectional study was conducted retrospectively by reviewed the patient’s medical record dan involved 41 subjects who were selected by consecutive sampling. Patient characteristics and therapy was analyzed descriptively and the variables relationship with retention rate was analyzed by using Spearman’s correlation test.The results showed the retention rate at 6 months (4.9%), 9 months (12.2%), 12 months (19.5%), 24 months (26.8%), 36 months (26.8%) , 48 months (4.9%) and 60 months (4.9%). According to Spearman's correlation test, the smallest maintenance dose shows a significant correlation to the retention rate (p = 0.036 with sufficient correlation r = -0.382). Therefore, the selection of the smallest dose in patients undergoing MMTP needs a particular concern to increase the successfulness of this program, which is indicated by the retention rate in this study.